Pengaruh Media Game Edukasi Wordwall terhadap Motivasi Belajar IPAS Peserta Didik Kelas III SD - Theresia Winda Setyaningrum; Bayu Purba Sakti; Sri Suwartini (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
Learning motivation plays a crucial role in enhancing students’ engagement and academic achievement. However, science instruction in elementary schools is often dominated by conventional teaching methods that reduce student participation and interest. This study aimed to examine the effect of the Wordwall educational game on the science learning motivation of third-grade students at SD Negeri 1 Tegalyoso during the 2025/2026 academic year. A quantitative approach with a quasi-experimental method and a Non-Equivalent Control Group Design was employed. The sample consisted of 56 students, divided equally into experimental and control classes. Data were collected using a validated and reliable learning motivation questionnaire, supported by observation and documentation. Data were analyzed through descriptive statistics, normality and homogeneity tests, Paired Sample t-Tests, Independent Sample t-Tests, and N-Gain analysis. The results revealed that the experimental class achieved a significantly higher posttest motivation score (89.82) than the control class (67.32). The Independent Sample t-Test showed a significance value of 0.000 (< 0.05), while the N-Gain score reached 79.95% (high category) compared with 24.58% (low category) in the control class. These findings demonstrate that Wordwall effectively enhances elementary students’ science learning motivation.